Effect of profession collaboration training to malnutrition knowledge among health worker in South Sulawesi, Indonesia - ., Risnah; Hadju, Veni; Maria, Ida L.; Nontji, Werna; Sofingi, Imam; ., Yurniati (International Journal Of Community Medicine And Public Health, 2018)
Background: Malnutrition in children is a complex health problem that involves all health profession for handling it. Profession collaboration training is expected to increase the knowledge of health workers about profession collaboration on the malnutrition handling. The study aim was to assess the changing of profession collaboration knowledge on the malnutrition handling cases before and after training among health worker in Jeneponto district. Methods: We used Quasi experiment design with pre-test and post-test control group design in this study. The treatment group was given a module and training, while the control group was only given a module. Sampling technique was stratified random sampling. The knowledge measurement was conducted on baseline (pre-test), after training (post-test 1), and a month after training (post-test 2). Results: Friedman test showed that there was difference knowledge average about malnutrition before and after training in treatment group (p=0.006) and control group (p=0.006). In Wilcoxon analysis shows that there was a change of knowledge on before and after intervention (p=0.010) and knowledge on before and a month after intervention (p=0.013) in the treatment group. In Mann Whitney analysis shown that there was difference of knowledge between treatment group and control group (p=0.025) on pretest. But, there were no difference knowledge between treatment group and control group on post 1 (p=0.768) and post 2 (p = 0.206). Conclusions: Health education by training increased knowledge level about profession collaborassion on the malnutrition among health workers in Jeneponto district.